Mechanisms of GaAs atomic layer epitaxy: a review of progress - Heitzinger, John M; White, J.M; Ekerdt, J.G (Surface science, 1994)
In this article we review the surface chemistry of several precursors for the growth of GaAs. Specifically, we discuss trimethylgallium, triethylgallium, and arsine. Our discussion focuses on the importance of surface chemistry in achieving atomic layer epitaxy (ALE) of GaAs. While ALE has been the subject of numerous publications, a thorough understanding of the mechanism(s) of GaAs ALE has not been attained. We wish to illustrate how surface science experiments have helped in the search for a complete understanding. More generally, the results discussed in this paper are relevant to gas source molecular beam epitaxy, metal organic molecular beam epitaxy, organometallic vapor phase epitaxy, and chemical beam epitaxy.